Comparison of Chlamydia trachomatis infection among infertile and fertile women in Ahvaz, Iran: A case-control study - Fatemeh Joolayi; Tahereh Navidifar; Razieh Mohammad Jaafari; Mansour Amin (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Chlamydia trachomatis (C. trachomatis) is the main cause of bacterial sexually transmitted infections. In women, this infection can lead to tubal infertility. Objective: In this study we investigated C. trachomatis among infertile and fertile women with both polymerase chain reaction (PCR) and ELISA methods in Ahvaz, Iran. Materials and Methods: This case-control study was conducted at the Infertility Clinic of University Jahad, Ahvaz, Iran from January to August 2017. A total of 225 vaginal swabs and blood samples (100 infertile and 125 fertile women) were collected. Detection of C. trachomatis DNA was performed from vaginal swabs by amplification of MOMP gene. Also, anti C. trachomatis immunoglobulin M (IgM) and immunoglobulin G antibodies in the serum samples were recognized by enzyme-linked immunosorbent assay (ELISA). Results: Results showed that, 6 (6%) infertile and 2 (1.6%) fertile women were positive for IgM (p=0.21). Also, PCR was positive for C. trachomatis infection in 5 infertile (5%) and 2 fertile women (1.6%) (p=0.35). We did not find any seropositive immunoglobulin G in both groups. Conclusion: In this study, no significant difference was found between fertile and infertile groups for C. trachomatis infection. Also, the correlation between IgM and PCR results revealed a relatively strong agreement and seems both PCR and IgM assays are appropriate for the accurate diagnosis of C. trachomatis infections.